Massive pulmonary embolism and thrombolysis in an unsuspected pregnancy. (18th April 2012) - Ciantar, E; Norfolk, D; Simpson, N
Abstract : Background: Systemic thrombolysis in pregnancy is considered to be a high-risk treatment. Small trials in non-pregnant patients suggest a reduction in mortality when thrombolysis is used for massive PE.1 It is rarely used in pregnancy with only 13 cases reported in the English literature, of which there were no maternal deaths, four non-fatal maternal major bleeding complications, two foetal deaths and five preterm deliveries.2 Case Report: We report the case of a 21-year-old lady who presented to A&E with extreme breathlessness and tightness in the chest while playing netball. A CT venogram revealed a massive 'saddle embolus' in the main pulmonary trunk extending to the right pulmonary artery. There were also scattered emboli in the left pulmonary artery and severe right heart strain. It also revealed an unsuspected 25 week gestation. By the time the pregnancy was diagnosed she had been thrombolysed with recombinant tissue plasminogen activator with very good effect and subsequently continued on therapeutic tinzaparin. She presented to delivery suite at 33 weeks with contractions followed by a quick vaginal delivery (Apgars 71, 85), sustaining a 1000ml postpartum haemorrhage which was treated conservatively. Warfarin was commenced after delivery and continued for a further 3 months. She made a remarkable recovery with no evidence of pulmonary hypertension.